Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Aset terhadap Nilai Perusahaan dengan Struktur Modal Sebagai Variabel Intervening pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Reni Elwisri; Lusiana Lusiana; Putri Azizi (Universitas 45 Surabaya, 2024)
This research aims to determine the influence of profitability, company size and asset structure on company value with capital structure as an intervening variable in property & real estate companies listed on the Indonesian Stock Exchange for the 2018-2022 period. This research uses quantitative methods. The population in this research is all Property & Real Estate Companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sample in this study met the criteria and was determined using the Purposive Sampling method so that a total sample of 43 sample companies was obtained. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is Multiple Linear Regression Analysis using SPSS 29.0. The results of this research partially show that Profitability has a significant effect on Capital Structure, Company Size has a significant effect on Capital Structure, Asset Structure has a significant effect on Capital Structure, Profitability has a significant effect on Company Value, Company Size has a significant effect on Company Value, Asset Structure has no significant effect on Company Value, Capital Structure does not have a significant effect on Company Value, Capital Structure cannot mediate Profitability on Company Value, Capital Structure can mediate Company Size on Company Value, Capital Structure cannot mediate Asset Structure on Company Value in listed Property & Real Estate companies on the Indonesian Stock Exchange for the 2018-2022 period.